2015
DOI: 10.1016/j.alcr.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Within-couple specialisation in paid work: A long-term pattern? A dual trajectory approach to linking lives

Abstract: Research on the division of labour has mainly focussed on transitions between individuals' labour market states during the first years of parenthood. A common conclusion has been that couples specialize--women in unpaid and men in paid work--either due to gender ideologies or a comparative advantage in the labour market. But what happens later in life? The German Socio-Economic Panel now provides researchers with a continuous measure of working hours across decades of couples' lives, enabling a dual trajectory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…In principle, divisions of labor established early in life can develop over the life course in three ways: persistence, change or accumulation/reinforcement. To date, research on the stability and change of couples' division of paid work over the life course has strongly focused on the impact of crucial life events, prominently the transition to parenthood (e.g., Kühhirt, 2012;Langner, 2015). The findings support a more traditional division of paid labor after the birth of the first child, even among previously gender-egalitarian couples.…”
Section: Educational Assortative Mating and Couples' Division Of Markmentioning
confidence: 98%
See 3 more Smart Citations
“…In principle, divisions of labor established early in life can develop over the life course in three ways: persistence, change or accumulation/reinforcement. To date, research on the stability and change of couples' division of paid work over the life course has strongly focused on the impact of crucial life events, prominently the transition to parenthood (e.g., Kühhirt, 2012;Langner, 2015). The findings support a more traditional division of paid labor after the birth of the first child, even among previously gender-egalitarian couples.…”
Section: Educational Assortative Mating and Couples' Division Of Markmentioning
confidence: 98%
“…4 The age of the youngest (or last) child at the moment of the survey consists of the categories youngest age tertile, medium age tertile and oldest age tertile, complemented by dummy variables for the number of children. 5 Less traditional women postpone marriage and parenthood to establish careers (Langner, 2015). Hence, male breadwinner arrangements would be less likely among older couples with no or few children or who had children late.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…She found that even in this setting, and at a conservative estimate, a surprisingly small number of couples—only one‐fifth—adopted full specialization in later life, whereas a full third moved into (or back into) dual, full‐time employment. This trend is even more pronounced among highly educated couples: Half of those couples moved into dual full‐time employment (Langer, ). A longitudinal perspective, then, informs us that the specialization that might occur around childbearing ages is in many cases reversed later in the life course.…”
mentioning
confidence: 99%